A new species of Collodiscula (Xylariaceae) from China - Li, Qirui; Wen, Ting-Chi; Kang, Ji-Chuan; Hyde, Kevin D. (Phytotaxa, 2015)
A Collodiscula isolate, found on a bamboo stalk in China, differs from C. japonica by having smaller ascospores. On the basis of morphology and molecular phylogeny it is described as a new species, Collodiscula bambusae sp. nov.